L-Arginine Supplementation and Metabolism in Asthma - Angela Linderholm; Nicholas J. Kenyon; Erin O'Roark; Vivian W. Kwan; Jennifer M. Bratt; Michael Last (MDPI AG, 2011)
L-Arginine, the amino acid substrate for nitric oxide synthase, has been tested as a therapeutic intervention in a variety of chronic diseases and is commonly used as a nutritional supplement. In this study, we hypothesized that a subset of moderate to severe persistent asthma patients would benefit from supplementation with L-arginine by transiently increasing nitric oxide levels, resulting in bronchodilation and a reduction in inflammation. The pilot study consisted of a 3 month randomized, double-blind, placebo-controlled trial of L-arginine (0.05 g/kg twice daily) in patients with moderate to severe asthma. We measured spirometry, exhaled breath nitric oxide, serum arginine metabolites, questionnaire scores, daily medication use and PEFR with the primary endpoint being the number of minor exacerbations at three months. Interim analysis of the 20 subjects showed no difference in the number of exacerbations, exhaled nitric oxide levels or lung function between groups, though participants in the L-arginine group had higher serum L-arginine at day 60 (2.0 ± 0.6 × 10−3 vs. 1.1 ± 0.2 × 10−3 µmol/L, p < 0.05), ornithine at day 30 (2.4 ± 0.9 vs. 1.2 ± 0.3 µmol/L serum, p < 0.05) and ADMA at day 30 (6.0 ± 1.5 × 10−1 vs. 2.6 ± 0.6 × 10−1 µmol/L serum, p < 0.05) on average compared to the placebo group. The study was terminated prematurely. Supplementing asthma subjects with L-arginine increases plasma levels; whether subgroups might benefit from such supplementation requires further study.